2002 reports related to the OECD Model Tax Convention - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 2003)
This publication includes three recent reports of the Committee on Fiscal Affairs that resulted in changes to the OECD Model Tax Convention on Income and Capital. The first considers how to address situations where it would seem inappropriate to grant the benefits of tax treaties. The second examines the characterization of various types of electronic commerce payments under tax conventions. The third provides background for changes made to the Commentary on Article 5.
Restricting the entitlement to treaty benefits -- Treaty characterisation issues arising from E-Commerce: report adopted by the Committee on Fiscal Affairs -- Issues arising under Article 5 (Permanent Establishment) of the Model Tax Convention.
Includes bibliographical references
Keywords: Double taxation; Double taxation -- Treaties; Electronic commerce -- Taxation